Smart Thin Hydrogel Coatings Harnessing Hydrophobicity and Topography to Capture and Release Cancer Cells. Issue 34 (13th June 2016) - Wang, Luying; Liu, Hongliang; Zhang, Feilong; Li, Guannan; Wang, Shutao
Abstract : Smart thin hydrogel coatings are fabricated to capture and release targeted cancer cells by simultaneously tuning surface hydrophobicity and topography. At physiological temperature, the targeted cancer cells are captured on the hydrophobic and wrinkled coating surface. At room temperature, the captured cells are released from the hydrophilic and smooth coating surface.